Leadership Strategies in Addressing Out-of-School Children: A Comparative Study of Heads of Government and Public-Private-Managed Schools in Sindh, Pakistan - Irfan Ahmed Rind (MDPI AG, 2024)
The issue of Out-of-School Children (OOSC) presents a significant policy challenge in Sindh, Pakistan, where 44% of 5-16-year-olds are not attending school. This study examines how different leadership strategies in government and Public-Private Partnership (PPP) schools address this crisis. Drawing on transformational leadership theory and institutional theory, this research investigates the influence of school governance structures-specifically government schools, Education Management Organizations (EMOs), and Sindh Education Foundation (SEF) schools-on school leaders' abilities to increase student enrollment and retention. Through a multiple case study design, this study collects qualitative data from three school heads, augmented by perspectives from vice principals and teachers. The findings indicate that leadership agency is constrained in government schools due to centralized decision-making, while PPP schools, particularly SEF schools, offer more autonomy, enabling more adaptive and community-centered leadership strategies. This study concludes that decentralized governance in SEF schools is more effective in addressing the OOSC issue, particularly in marginalized areas. These findings offer valuable insights for policymakers seeking to enhance educational access in regions with similar socio-economic challenges. The implications of this research underscore the need for flexible, context-specific leadership models to combat the OOSC crisis.